Relationship between human development competencies and work performance - Tiraieyari, Neda; Idris, Khairuddin; Uli, Jegak; Hamzah, Azimi (American-Eurasian Network for Scientific Information, 2011)
This research investigates the relationship between human development competencies in terms of leadership development and problem solving/ decision making development and work performance among Malaysian extension workers at the department of agriculture with the emphasis of having human development competencies in order to perform the extension work well. Stratified random sampling technique employed to select 210 extension workers from the department of agriculture in four states of Malaysia. A structured research instrument was utilized to survey extension workers' human development competencies and work performance. The data were analyzed using descriptive statistics and Pearson correlation analysis. Extension workers reported high level of leadership development competency and problem solving/decision making development competency. The findings supported a positive relationship between human development competencies and work performance.